Influence of several oenological fining agents on ochratoxin A removal - Carvalho, Filipa (2014)
In Europe, wine is estimated to be the second source, after cereals, of ochratoxin A (OTA), one of the most important mycotoxin found in food and feed products [1]. Its chemical structure consists of a chlorine-containing dihydro-isocoumarin linked through the 7-carboxyl group to L--phenylalanine. In wine, this fungal metabolite represents a severe risk for consumer health. According to the European Commission Regulation (EC) No. 123/2005 the maximum limit for OTA in wine is 2 g/Kg [2]. Therefore, it is important to prevent and control their occurrence in wines. With the purpose to remove this toxin, several chemical, microbiological and physical methods were described in the literature [1, 3, 4]. Consequently, the aim of this work is to understand the interaction of different types of fining agents on OTA removal from wine. To evaluate their effectiveness, eleven commercial fining agents, including mineral, synthetic, animal and vegetable proteins were used to get new approaches on OTA removal from wine. Trials were performed in wines added of OTA. Most effective fining agent in removing OTA was a commercial formulation that contains activated carbon, a well-known adsorbent of mycotoxins. Reductions between 10 and 30% were also obtained with potassium caseinate, yeast cell walls and pea protein. However, with bentonites, carboxymethylcellulose (CMC), polyvinylpolypyrrolidone (PVPP) and chitosan no considerable reduction of OTA was verify. Also, the influence of these fining agents on the physicochemical wine characteristics, namely wine color, total phenolic compounds, flavonoids and non-flavonoids were studied. Final results could provide important information to the wine industry to select treatments based on fining agents to remove OTA, in order to reduce toxicity and consequently to improve wine safety and preserving wine quality.